VISUALISASI PENERAPAN PROSES MULTITHREADING PADA METODE INTERNAL SORTING - Andri Sukmaindrayana (LPPM STMIK DCI, 2014)
Multithreading is an ability that allows a set of instructions (process) run simultaneously (time slicing) in a program. Sorting is a process to reconstruct an object using a set of specific rules. Sorting is also known as an algorithm to put a collection of data elements into a particular order based on one or more keys in each element.Basically there are two kinds of sequences are commonly used in the sorting process :1. ride sequence (ascending), sort of data that has the smallest value to the largest;2. sequence down ( descending ) , sort of data that have the greatest value to the smallest .Visualization (UK : visualization) is in the manufacture of engineering drawings, diagrams, or animations to appearance information. In general, visualization in the form of images both abstract and real has been known since the beginning of human civilization. Examples of this include the paintings on the walls of the caves of ancient humans, form letters hiroglip Egyptian, Greek geometry systems, and techniques of Leonardo da Vinci's painting for engineering and scientific purposes, etc.Keyword : Multithreading, Sorting, Visualization.